Anthropogenic land subsidence in the Perth Basin: Challenges for its retrospective geodetic detection - Featherstone, Will; Filmer, Michael; Penna, N.; Morgan, L.; Schenk, A. (Royal Society of Western Australia, 2012)
Recent-past subsidence of parts of the Perth Basin has most probably been caused by increased groundwater extraction for domestic and agricultural use. However, no dedicated geodetic monitoring programs were established when the increased extraction began in around 2000, thus setting a challenge to retrospectively quantify and map the subsidence. Differential levelling is likely to be less effective as only a few repeat traverses cover the areas thought to be subsiding. Repeat gravimetry is totally ineffective because of microseismic vibrations propagating through the Perth Basin. Repeat episodic GPS (Global Positioning System) is also likely to be less effective because of the few station occupations over several days or weeks and the inherent weakness of GPS for height determination. However, from a continuously operating GPS receiver at Gnangara and nearby artesian monitoring boreholes, we show that the rate of land subsidence has slowed from about -6 mm/yr to about -2 mm/yr since the reduction of groundwater extraction from the Yarragadee Aquifer in around 2005. A promising technique is InSAR (interferometric synthetic aperture radar) because it can map large areas, but the lack of historical radar imagery over the period of increased subsidence is a hindrance.